2019
DOI: 10.3390/antiox8120586
|View full text |Cite
|
Sign up to set email alerts
|

Saffron Processing Wastes as a Bioresource of High-Value Added Compounds: Development of a Green Extraction Process for Polyphenol Recovery Using a Natural Deep Eutectic Solvent

Abstract: The current investigation was undertaken to examine saffron processing waste (SPW) as a bioresource, which could be valorized to produce extracts rich in antioxidant polyphenols, using a green, natural deep eutectic solvent (DES). Initially, there was an appraisal of the molar ratio of hydrogen bond donor/hydrogen bond acceptor in order to come up with the most efficient DES composed of L-lactic acid/glycine (5:1). The following step was the optimization of the extraction process using response surface methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 41 publications
6
69
1
Order By: Relevance
“…Diffusivity may be increased by raising R L/S [27]; however, the optimum R L/S found for polyphenol extractions with DES may vary from 29.5 [28] to as high as 100 mL g −1 dm [29,30]. The optimal R L/S determined for EBF (60 mL g −1 ) is in accordance with recent studies on polyphenol extraction with DES from saffron processing wastes (60 mL g −1 ) [15] and hop (59 mL g −1 ) [13].…”
Section: Optimization Of Extraction Performancesupporting
confidence: 87%
See 4 more Smart Citations
“…Diffusivity may be increased by raising R L/S [27]; however, the optimum R L/S found for polyphenol extractions with DES may vary from 29.5 [28] to as high as 100 mL g −1 dm [29,30]. The optimal R L/S determined for EBF (60 mL g −1 ) is in accordance with recent studies on polyphenol extraction with DES from saffron processing wastes (60 mL g −1 ) [15] and hop (59 mL g −1 ) [13].…”
Section: Optimization Of Extraction Performancesupporting
confidence: 87%
“…On the other hand, optimization of polyphenol extraction has shown that, in some cases, low S S (300 rpm) may favor increased extraction yield, as opposed to higher S S (900 rpm), which apparently was hindering in this regard [30]. In other recent examinations, the findings indicated quite the opposite [15,29]. Since the phenomena associated with the effect of S S may be related with factors such as the nature of the solid material, the solid particle diameter, the solute (polyphenols species), the viscosity of the liquid phase (solvent), etc., the actual effect of S S on extraction yield would be a subject of case experimentation.…”
Section: Optimization Of Extraction Performancementioning
confidence: 93%
See 3 more Smart Citations